Design of real-time actuated control system for modern tram at arterial intersections based on logic rules. (December 2018) - Li, Yun; Cai, Qiyan; Xu, Yujie; Shi, Weihua; Chen, Yibao
This article is on the purpose of developing an isolated tram signal priority control strategy based on logic rule for modern tram system. The designed method is presented with features that can ensure the intersection operates in a proper manner on the premise of tram priority and avoid vehicle queue overflow when the tram passes. In this study, the new method description consists of two parts: (1) the detector locations are determined, which include the upstream detector, the upstream trigger detector, the downstream detector, and the queuing detector upon entry approach to the intersection; (2) the corresponding priority logical algorithm for signal control is designed. The proposed method is experimentally examined in a tram intersection in Huaian city, China. In the process of the experiment, the detector layout scheme and optimal priority control model are simulated and verified using the VisVAP module of the Vissim simulation software. In the experimental results, the designed scheme significantly decreases average delay than the fixed timing signal control method, while it also can prevent the vehicle queue from overflowing compared to the absolute priority actuated control scheme.